Structural and cryogenic magnetic properties of the RE2MoO6 (RE = Er and Ho) compounds. Issue 5 (1st March 2023) - Wang, Pengyu; Zhang, Yingde; Huang, Jiaohong; Hu, Liang; Wang, Xinhua; Li, Lingwei; Yan, Mi
Abstract: The rare earth ( RE ) based magnetic materials with large low temperature magnetocaloric effect (MCE) have attracted much research interest due to their potential application for the environment-friendly magnetic refrigeration (MR) technology. Herein, a systematic investigation on the crystal structure, micro morphology together with the low temperature magnetic properties and MCE performances have been conducted on the RE 2 MoO6 ( RE  = Er and Ho) compounds. Both compounds crystallize in monoclinic structure and exhibit large reversible low temperature MCE. The maximum magnetic entropy changes ( − Δ S M max ) at magnetic field change ( Δ H ) of 0–5 T reach 15.3 and 15.8 J kg −1  K −1 for Er2 MoO6 and Ho2 MoO6, respectively. The corresponding relative cooling power/refrigeration capacity ( RCP / RC ) values are 197.4/149.7 and 286.0/222.3 J/kg. These obtained MCE parameters for present RE 2 MoO6 compounds are close to those of reported RE based MCE materials, which make them of potential for low temperature MR application.